The effect of cigarette smoking on salivary IgA and periodontal disease - Ali, Omar H (Journal of Baghdad College of Dentistry, 2015)
Background: Chronic periodontitis is an inflammatory disease of tissues supporting the teeth. Salivary compositions have been most intensely studied as a potential marker for periodontal disease. In this study, analysis of saliva provides a simple and non-invasive method of evaluating the role of salivary IgA (s-IgA) levels in periodontal disease by detecting the level of (s-IgA) in patients with chronic periodontitis smokers and non smokers patients and correlate the mean (s-IgA) levels with clinical periodontal parameters Plaque index (PLI) gingival index (GI), probing pocket depth (PPD) and clinical attachment level (CAL).Materials and Methods: The study samples consists of (15) patients with chronic periodontitis who were non smokers (Group I) and (15) patients with chronic periodontitis who were smokers (Group II) of both gender with an age ranged (35-45) years were the periodontal parameters used in this study (PLI, GI, PPD and CAL), unstimulated salivary sample were collected from all subjects and the levels of salivary IgA (s-IgA) in each sample were analyzed for each group by using enzyme-linked immunosorbent assay (ELISA) technique. A statistical analysis was done by using excel 2013.Results: There was a significant difference with high mean level in the clinical periodontal parameters in smokers group compared to non smokers with chronic periodontitis (PLI, PPD and CAL) except GI which showed no significant difference between the same groups. The biochemical finding showed significant difference with low mean level for (s-IgA) in smokers group compared to non smokers. Conclusion: The findings in this study showed that the concentrations of salivary IgA might be used as an indicator for periodontal disease progression in smokers with chronic periodontitis as a resultant to the effect of smoking which lowering the concentration of the salivary IgA and subsequent reducing of the host’s defense lead to increase in the progression of periodontal disease.